Keabsahan Perkawinan Penghayat Kepercayaan Sunda Wiwitan Berdasarkan Undang-Undang Perkawinan dan Undang-Undang Administrasi Kependudukan - Farahdyba Refitha Putri (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2017)
Farahdyba Refitha P, Warkum Sumitro, S.H., M.H., Diah Pawestri Maharani, S.H.,M.H. Fakultas Hukum Brawijaya Email: Farahdyba94@gmail.com Â  ABSTRAK Masyarakat adat adalah masyarakat yang memiliki kepercayaan asli dari nenek moyang, bahkan sampai saat ini masih ada masyarakat adat yang tetap memegang teguh kepercayaan asli tersebut dan oleh Undang-Undang mereka disebut Penghayat Kepercayaan. Namun, keberadaan penganut Penghayat Kepercayaan masih mendapat diskriminasi oleh Badan Kantor Catatan Sipil (BKCS) karena di anggap bukan suatu agama. Banyak kendala yang dihadapi oleh para Penghayat Kepercayaan terkait kedudukan status hukum mereka di mata Negara, terutama mengenai masalah pencatatan perkawinan. Undang-undang Nomor 1 Tahun 1974 tentang Perkawinan tidak mengatur tentang perkawinan Penghayat Kepercayaan. Akibatnya, para penghayat kepercayaan kerap mendapatkan penolakan pencatatan perkawinan dari Kantor Catatan Sipil setempat. Penelitian ini bertujuan untuk mengidentifikasi dan menganalisis mengenai keabsahan perkawinan bagi penganut penghayat kepercayaan sunda wiwitan berdasarkan Undang-Undang Nomor 1 Tahun 1974 tentang Perkawinan, serta mengidentifikasi dan menganalisis implikasi yuridis perkawinan bagi penganut penghayat kepercayaan sunda wiwitan berdasarkan Peraturan Pemerintah nomor 37 Tahun 2007 tentang Pelaksanaan Undang-Undang Nomor 23 Tahun 2006 tentang Administrasi Kependudukan. Penelitian ini merupakan penelitian yuridis normatif, dengan menggunakan metode pendekatan perundang-undangan, pendekatan kasus dan pendekatan konseptual. Hasil penelitian menunjukkan permasalahan yang terjadi adalah penolakan pencatatan perkawinan oleh Kantor Catatan Sipil, atas dasar kepercayaan Sunda Wiwitan, bukan merupakan agama, sehingga terdapat kesenjangan antara pelaksanaan (das sein) dan pengaturan (das solen). Kata kunci: Kepercayaan, Perkawinan, Penghayat KepercayaanÂ  ABSTRACT Indonesian society is a traditional society who preserves their ancestors belief, even there is still an indigenous people still uphold the original beliefs and constitution called â€œPenghayat Kepercayaan. However, until now the existence of â€œPenghayat Kepercayaanâ€got discrimination by some people because these beliefs are not classified as religion. Obstacle are familiar to the people of â€œPenghayat Kepercayaanâ€, in regards to the lega status according to Indonesian Law, especially relating to issues of marriageâ€™s registration. Indonesian law Number 1 year 1974 regarding marriage does not regulate the marriage of â€œPenghayat Kepercayaanâ€ people. As a result, people of â€œPenghayat Kepercayaanâ€ received several rejections of marriage records from the local Civil Registry Office. Purpose of this reasearch is analyze the the validity of marriage to â€œPenghayat Kepercayaan Sunda Wiwitanâ€ based on the act number 1 of 1974 about the Law of marriage, and identifying and analyzing juridical marriage implications for â€œPenghayat Kepercayaan Sunda Wiwitanâ€ based on government regulation number 37 of 2007 on the implementation of the act number 23 of 2006 about The Law Of Civil Registration. Kinds of this reaserach is normative reasearch, with statue approach, case approach,Â  and conceptual approach methods. The result shows what happen is the rejection of recording marriage by local Civil Registry Office, based on â€œKepercayaan Sunda Wiwitanâ€Â  is not a religion, so there are the gap between the implementation ( das sein) and the arrangement (das solen). Keyword: Beliefs, Marriage, Penghayat Kepercayaan .Indonesian people have original believe from their ancestor. Even up to now, the indigenous people are strong believers of those beliefs and the law entitles them with the believers (penghayat kepercayaan). Unfortunately, those believers suffer from discrimination by certain parties because their belief is not considered a religion. The believers encounter many problems related to their legal status in front of state, especialy on the marriage resgistration. Law number 1 year 1974 about Marriage does not regulate the marriage of those believers. As the result, the believers often suffer from rejection on marriage registration from the Civil Registration Office. Indonesia has formulated a law about the believers on Law number 23 year 2006 about population administration. Further, the marriage of the believers is also regulated under Goverment Regulation number 37 year 2007. Thus, the believers can now register their marriage in Civil Registration Office. This study used normative juridical method through legal materials in the forms of journals,documents, and literature. Keywords : beliefs.marriage,believersIndonesian people have original believe from their ancestor. Even up to now, the indigenous people are strong believers of those beliefs and the law entitles them with the believers (penghayat kepercayaan). Unfortunately, those believers suffer from discrimination by certain parties because their belief is not considered a religion. The believers encounter many problems related to their legal status in front of state, especialy on the marriage resgistration. Law number 1 year 1974 about Marriage does not regulate the marriage of those believers. As the result, the believers often suffer from rejection on marriage registration from the Civil Registration Office. Indonesia has formulated a law about the believers on Law number 23 year 2006 about population administration. Further, the marriage of the believers is also regulated under Goverment Regulation number 37 year 2007. Thus, the believers can now register their marriage in Civil Registration Office. This study used normative juridical method through legal materials in the forms of journals,documents, and literature. Keywords : beliefs.marriage,believers